2000
DOI: 10.1002/(sici)1097-4628(20000725)77:4<711::aid-app1>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Some peculiar features of radiation grafting of monomers of various structures and reactivities onto polyolefins

Abstract: Some peculiar features were studied for radiation grafting of monomers of various structures and reactivities in radical polymerization onto polyolefins (polyethylene and polypropylene). From the point of view of the kinetics and mechanism of grafting, the monomers are divided into two classes: The first class includes all monomers active in radical polymerization. When irradiated together with the polymeric matrix, they are grafted onto it as long polymeric chains and parallel to this occurs homopolymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Spencer et al investigated the grafting of vinyltrimethoxysilane (VTMS) onto PE and found that the monomer was not grafted homogeneously, but was concentrated in " clusters " generated by chain transfer from a VTMS radical to a nearby site liable to H -abstraction, which was then able to add additional VTMS (Scheme 3.7 ) [52] . R ä tzsch et al found that a large number of nonhomopolymerizable monomers giving short chains onto polypropylene also gave these " nests " or " clusters " of grafting sites (vinyltriethylsiloxane, monovinyl ester of ethylene glycol, vinyl butyl ether, vinyl isobutyl ether) [48] . The overall result of maintaining an unreactive polymer radical in these zones, instead of reactivity being transferred to a more reactive polymer radical, is to enhance crosslinking over grafting [53] .…”
Section: Effect Of the Monomersupporting
confidence: 79%
See 1 more Smart Citation
“…Spencer et al investigated the grafting of vinyltrimethoxysilane (VTMS) onto PE and found that the monomer was not grafted homogeneously, but was concentrated in " clusters " generated by chain transfer from a VTMS radical to a nearby site liable to H -abstraction, which was then able to add additional VTMS (Scheme 3.7 ) [52] . R ä tzsch et al found that a large number of nonhomopolymerizable monomers giving short chains onto polypropylene also gave these " nests " or " clusters " of grafting sites (vinyltriethylsiloxane, monovinyl ester of ethylene glycol, vinyl butyl ether, vinyl isobutyl ether) [48] . The overall result of maintaining an unreactive polymer radical in these zones, instead of reactivity being transferred to a more reactive polymer radical, is to enhance crosslinking over grafting [53] .…”
Section: Effect Of the Monomersupporting
confidence: 79%
“…Monomers that readily homopolymerize will encourage grafting over crosslinking, and are more likely to generate signifi cant amounts of homopolymer (e.g., butyl acrylate); monomers that are reluctant to homopropagate will give short grafts and may enhance crosslinking (e.g., ethyl maleate) [37,48] .…”
Section: Effect Of the Monomermentioning
confidence: 99%
“…The increase of the grafting yield with the benzene content of the grafting solution is probably due to a facilitated diffusion of the monomer through the macromolecular VP–DMAM‐grafted chains. It is well known that the diffusibility of the monomer diluents into the polymer matrix has a great influence on the grafting process and grafting yield 36. Thus, the grafting process proceeds by a front mechanism in which the grafted layers initially formed on the polymeric surface can swell in the monomer–diluent mixture, resulting in more progressive diffusion of the monomer into the interior regions of the PP spheres.…”
Section: Resultsmentioning
confidence: 99%
“…Although various monomers have been successfully grafted onto polyolefin, reports of silane grafting by solid‐state modification are rare. Rätzsch et al [12] studied irradiation grafting of monomers with various structures onto PE and PP and found out that graft degree of vinyl alkoxy silanes turned to be low, while VS did not tend to form long polymeric chains in grafting processes especially at room temperature and low dose rates because of high transfer rate. Jain [13] reported the synthesis of PP/silica nanocomposites by combining solid‐state modification of PP with vinyltriethoxysilane (VTES) and sol–gel technology with the idea that grafted monomeric VTES could be incorporated in the silica particles during the sol–gel reaction to control the matrix filler adhesion.…”
Section: Introductionmentioning
confidence: 99%